2020
DOI: 10.1007/s10295-020-02330-3
|View full text |Cite
|
Sign up to set email alerts
|

Time-course transcriptomics reveals that amino acids catabolism plays a key role in toxinogenesis and morphology in Clostridium tetani

Abstract: Tetanus is a fatal disease caused by Clostridium tetani infections. To prevent infections, a toxoid vaccine, developed almost a century ago, is routinely used in humans and animals. The vaccine is listed in the World Health Organisation list of Essential Medicines and can be produced and administered very cheaply in the developing world for less than one US Dollar per dose. Recent developments in both analytical tools and frameworks for systems biology provide industry with an opportunity to gain a deeper unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Despite its differential expression by culture conditions and time, expression of tetX was always high and relatively stable during and between cultures (Figure 2), which shows that growth phase and conditions only affected tetX expression to a limited extent. This contrasts with the findings described by Licona-Cassani et al [6], which were later confirmed by Orellana et al [20]. Licona-Cassani et al found that tetX expression is triggered by the transition from amino acid consumption to peptide consumption, corresponding to a switch to a slower growth rate at around 10 h of culture.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Despite its differential expression by culture conditions and time, expression of tetX was always high and relatively stable during and between cultures (Figure 2), which shows that growth phase and conditions only affected tetX expression to a limited extent. This contrasts with the findings described by Licona-Cassani et al [6], which were later confirmed by Orellana et al [20]. Licona-Cassani et al found that tetX expression is triggered by the transition from amino acid consumption to peptide consumption, corresponding to a switch to a slower growth rate at around 10 h of culture.…”
Section: Discussionmentioning
confidence: 77%
“…In other Clostridium species, as well as other bacteria, prophage genes can influence cellular lysis (which leads to the release of TeNT into the medium) as well as regulate toxin gene transcription [23,24]. In fact, Orellana et al found that two genes (CTC_RS05470 and CTC_RS07675) located in different prophage insertion regions in the C. tetani genome clustered with the transcription of the tetX transcriptional regulator BotR [20]. It is therefore conceivable that further research on this prophage region may lead to new insights into TeNT regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to variations in toxin production according to different media, variations in BoNT or TeNT yields are often observed from batch to batch of the same culture medium, even using the same bacterial strain. The transcription of neurotoxin genes and toxin synthesis occur mainly within a short time interval between the late exponential growth and early stationary growth phase [33,85,86]. Thus, nutritional and environmental factors influence the regulation of toxin synthesis in C. botulinum and C. tetani, which takes place in a restricted phase of bacterial growth.…”
Section: Amino Acid/peptide Metabolismmentioning
confidence: 99%
“…Peptides and amino acids appear to be important regulatory factors at the transcriptional and posttranscriptional levels. Indeed, large amounts (0.8-0.9 g/L) of amino acids (aspartate, glutamate, serine, histidine, threonine) downregulate tetR and tent by a yet non-identified regulatory pathway [86]. Arginine is an essential amino acid for C. botulinum growth, but an excess of arginine represses BoNT production in proteolytic group I C. botulinum [87].…”
Section: Amino Acid/peptide Metabolismmentioning
confidence: 99%
See 1 more Smart Citation